MicroRNA-Based Therapy in Animal Models of Selected Gastrointestinal Cancers - Merhautova, Jana; Demlova, Regina; Slaby, Ondrej (Frontiers in Pharmacology, 2016)
Gastrointestinal cancer accounts for the 20 most frequent cancer diseases worldwide and there is a constant urge to bring new therapeutics with new mechanism of action into the clinical practice. Quantity of in vitro and in vivo evidences indicate, that exogenous change in pathologically imbalanced microRNAs (miRNAs) is capable of transforming the cancer cell phenotype. This review analyzed preclinical miRNA-based therapy attempts in animal models of gastric, pancreatic, gallbladder, and colorectal cancer. From more than 400 original articles, 26 was found to assess the effect of miRNA mimics, precursors, expression vectors, or inhibitors administered locally or systemically being an approach with relatively high translational potential. We have focused on mapping available information on animal model used (animal strain, cell line, xenograft method), pharmacological aspects (oligonucleotide chemistry, delivery system, posology, route of administration) and toxicology assessments. We also summarize findings in the field pharmacokinetics and toxicity of miRNA-based therapy.